The 8051 microcontroller a systems approach - Mazidi, Muhammad Ali; Mazidi, Janice Gillispie; McKinlay, Rolin D. (Pearson, 2014)
The 8051 Microprocessor: A Systems Approach emphasizes the programming and interfacing of the 8051. Using a systematic, step-by-step approach, the text covers various aspects of 8051, including C and Assembly language programming and interfacing. Throughout each chapter, examples, sample programs, and sectional reviews clarify the concepts and offer students an opportunity to learn by doing.